Девочка - подросток - девушка: пособие для учителей / А. Г. Хрипкова, Д. В. Колесов - Хрипкова Антонина Георгиевна (Просвещение, 1981)
Экземпляры: (20150821) / Инвентарный номер: 342 / Сис.шифр: 613.9 / Авт.знак: Х 93 / ББК: 74.200.56